NUTRITIONAL ANALYSIS AND CHEMICAL FINGERPRINTING OF BLACK SOLDIER FLY (Hermetia illucens) LARVAE MEAL NATIVE TO THE PERUVIAN AMAZON - VARGAS-ARANA, Gabriel (2024)
The search for new protein sources for food formulation is increasing. Black soldier fly (Hermetia illucens) larvae have high levels of protein, good fat content and are rich in essential amino acids, making them an alternative source of dietary protein. In this work, the nutritional properties and metabolomic characterization of black soldier fly larvae meal native to the Peruvian Amazon reared on three organic waste substrates were carried out. The three meals had a high protein content (38.90-44.68%), lipids (26.96-31.01%), as well as a high potassium, calcium and low sodium content. The larvae meal fed with orange bagasse presented the best content of iron and manganese. The fatty acid profile showed a high content of palmitic, oleic and linoleic acids for the three flours. The most abundant essential amino acids in the three meals were leucine, lysine and valine. A total of 48 compounds were identified in the larvae meal fed with orange bagasse, 24 compounds in the larvae meal fed with oats and 44 compounds in the larvae meal fed with ripe banana pulp. These results indicate that black soldier fly larvae meals native to the Peruvian Amazon are a good source of proteins, minerals, essential amino acids and unsaturated fatty acids with high nutritional value.